2020
DOI: 10.1097/qad.0000000000002528
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk following lymphoid malignancies among HIV-infected people

Abstract: Objective(s): HIV-infected people have increased cancer risk. Lymphoma survivors have an increased risk of certain second primary cancers in the general population, but second cancer risk among HIV-infected people is poorly understood. Herein, we characterized the risk of cancers following lymphoid malignancies among HIV-infected people. Design: Population-based linkage of HIV and cancer registries. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
4
5
0
1
Order By: Relevance
“…These results were consistent with previous studies that identified a higher risk of developing NHL after KS among PLWH than among the general U.S. population [ 23 , 25 ], and a higher risk of developing KS after an AIDS-defining lymphoid malignancy [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results were consistent with previous studies that identified a higher risk of developing NHL after KS among PLWH than among the general U.S. population [ 23 , 25 ], and a higher risk of developing KS after an AIDS-defining lymphoid malignancy [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…In women, breast cancer was the most common SPC after primary NHL, which was in agreement with data of Mahal et al [ 24 ]. Additionally, as observed in the general population of French women [ 26 ], breast cancer was also the most common SPC after a primary breast cancer.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another recent registry-based linkage study that examined second cancers only after a lymphoid primary cancer in PLWHIV found an increase in the risk of nonlymphoid cancers. 33 This is consistent with our finding that EBV-related FPCs, most of which were non-Hodgkin lymphoma, were not associated with the increased incidence of an EBV-related SPC, but rather other SPCs dominated in this subset.…”
Section: Discussionsupporting
confidence: 92%
“…However, some human cancers are still frequently diagnosed in HIV-positive patients ( 5 ), and they are categorized into 2 different types: 1) non-AIDS-defining cancers, including Hodgkin lymphomas, which are associated with advanced age, smoking, race and low CD4+ count ( 6 ); and 2) AIDS-defining cancers, usually associated with oncogenic viruses ( 7 ). Regarding AIDS-defining cancers, previous studies indicate Kaposi’s sarcoma as the most prevalent neoplasm, followed by non-Hodgkin lymphomas ( 8 ).…”
Section: Introductionmentioning
confidence: 99%